A comparative study using solution analysis, electrochemistry and mass change for the inhibition of carbon steel by the plant alkaloid Voacangine. (17th February 2020) - Ngouné, Bertrand; Pengou, Martin; Nanseu-Njiki, Charles Peguy; Ngameni, Emmanuel
ABSTRACT: In this work, the plant alkaloid Voacangine, isolated from the bark of Tabernaemontana contorta, was examined as a corrosion inhibitor for steel in 1 M hydrochloric acid. The study was carried out using a comparative approach where several independent methods (spectroscopic solution analysis, electrochemical impedance, potentiodynamic polarisation and mass loss measurements) were performed in order to strengthen the validity of the results. All the findings revealed to be in close agreement with each other. Voacangine was determined to be a mixed corrosion inhibitor and to closely follow Langmuir-type adsorption onto active corrosion sites on the metal surface. The maximal inhibition efficiency was 90% which is lower than other comparable species. This deficiency was ascribed to the presence of a basic nitrogen group causing a degree of steric hindrance for the adsorption.